Pest risk assessment of Diaporthe vaccinii for the EU territory. (13th September 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navarro, Maria Navajas; et al.
Abstract: As requested by the European Commission, the EFSA Panel on Plant Health (PLH) Panel assessed the risk of Diaporthe vaccinii in the EU, focusing on entry, establishment, spread and impacts on cultivated and wild Vaccinium species, the principal hosts being American and European cranberry and blueberry. Several outbreaks occurred in the EU since 1956, but most were eradicated except in Latvia. The Panel considered entry via fruits and plants for planting. The risk of establishment from discarded infected berries is much lower than from infected plants for planting, of which, potted plants and cuttings pose the greatest risk, while plug plants, derived from tissue culture and grown in pest free structures, pose a low risk. Nine per cent of the EU is highly suitable for establishment of the pathogen, mostly in the SE and NE. Following establishment, the pathogen could spread naturally over short range, and by human assistance over long range. Calculations with an integrated model for entry, establishment and spread, indicate that with current regulations, over a period of 5 years, a few hundred cultivated Vaccinium plants and several thousand Vaccinium plants in natural ecosystems would contract the disease. The associated loss of commercial production is small, less than one tonne of berries per year. On natural vegetation, the median impact after 5 years was estimated to be negligible affecting a negligible proportion of the natural Vaccinium population (2 × 10 −8 ). However, the uncertainty of this estimate was high, due to uncertainty about the rate of spread; in a worst‐case scenario (99th percentile), almost 1% of plants in natural areas would become infected. Complete deregulation (scenario A1) was predicted to increase the impact substantially, especially in natural areas, while additional measures (scenario A2) would effectively eliminate the entry of infected plants for planting, further reducing the impacts below the current situation.